2020
DOI: 10.1096/fasebj.2020.34.s1.04622
|View full text |Cite
|
Sign up to set email alerts
|

In Defense of the “Entourage Effect”: Terpenes Found in Cannabis sativa Activate the Cannabinoid Receptor 1 In Vitro

Abstract: Marijuana has been understudied for decades, primarily due to social stigma and legal restrictions. However, as legal restrictions begin to loosen among states, the potential medical benefits and pharmacological properties of marijuana are beginning to be explored. Terpenes, an expansive group of organic chemicals that impart odor and taste, are found in the Cannabis sativa plant and may work synergistically with cannabinoids, such as THC and CBD, in a term deemed the “entourage effect”. Anecdotally among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Entourage effect refers to the joint effects of taking these cannabinoids together with other minor cannabinoids and phytochemicals called terpenes (volatile aromatic compounds) being more beneficial than just taking pure THC or pure CBD [ 17 , 18 ]. Trichomes (as shown in Figure 1 ), which are the microscopic glandular membranes found on the surface of the cannabis inflorescence, contain cannabinoids and terpenes that are vital for psychoactive and medicinal effects.…”
Section: Phytocannabinoids and Decarboxylationmentioning
confidence: 99%
“…Entourage effect refers to the joint effects of taking these cannabinoids together with other minor cannabinoids and phytochemicals called terpenes (volatile aromatic compounds) being more beneficial than just taking pure THC or pure CBD [ 17 , 18 ]. Trichomes (as shown in Figure 1 ), which are the microscopic glandular membranes found on the surface of the cannabis inflorescence, contain cannabinoids and terpenes that are vital for psychoactive and medicinal effects.…”
Section: Phytocannabinoids and Decarboxylationmentioning
confidence: 99%
“…Several studies have further supported this mechanism and demonstrated that all the compounds present in the cannabis plant work together to produce the therapeutic effect [26,27]. Blasco-Benito et al [27] demonstrated that the botanical drug preparation was more potent than pure ∆ 9 -THC in both in vitro and in vivo models of breast cancer.…”
Section: Cannabinoids and The Entourage Effectmentioning
confidence: 98%